2019
DOI: 10.1039/c8sm02160k
|View full text |Cite
|
Sign up to set email alerts
|

Ice-templated poly(vinylidene fluoride) ferroelectrets

Abstract: Ferroelectrets are piezoelectrically-active polymer foams that can convert externally applied loads into electric charge. Existing processing routes used to create pores of the desired geometry and degree of alignment appropriate for ferroelectrets are based on complex mechanical stretching and chemical dissolution steps. As a simple, cost effective and environmentally friendly approach, freeze casting is able to produce aligned pores with almost all types of the materials, including polymers. In this work, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…The PVDF-based piezoelectric devices currently reported are mainly two-dimensional (2D) thin-film or flat block structures. , The substrate of these structures has significant local residual stress, which will have a strong clamping effect on the movement of the dipole and the charge separation process, thereby reducing the effective piezoelectric coefficient. Compared with the 2D planar structure, construction of a three-dimensional (3D) structure has the following advantages: (1) The “nano-confinement” effect of structures such as holes and arrays can make the compressive stress uniformly distributed and restrain the strain in the vertical stress direction, which obviously alleviates clamping effect. , (2) The porous structure can greatly reduce the material modulus, amplify the deformation under the same stress, and effectively increase the piezoelectric output. (3) The structure of the device can be customized on demand, which promotes processing flexibility. , …”
Section: Introductionmentioning
confidence: 99%
“…The PVDF-based piezoelectric devices currently reported are mainly two-dimensional (2D) thin-film or flat block structures. , The substrate of these structures has significant local residual stress, which will have a strong clamping effect on the movement of the dipole and the charge separation process, thereby reducing the effective piezoelectric coefficient. Compared with the 2D planar structure, construction of a three-dimensional (3D) structure has the following advantages: (1) The “nano-confinement” effect of structures such as holes and arrays can make the compressive stress uniformly distributed and restrain the strain in the vertical stress direction, which obviously alleviates clamping effect. , (2) The porous structure can greatly reduce the material modulus, amplify the deformation under the same stress, and effectively increase the piezoelectric output. (3) The structure of the device can be customized on demand, which promotes processing flexibility. , …”
Section: Introductionmentioning
confidence: 99%
“…For decades, different types of moieties are used as a filler to ameliorate some of the limitations of a polymer to increase their applications. The usage of the polar molecules in a non-polar polymer not only led to high piezoelectricity but also affect the physical and electrical properties which had replaced the conventional ceramic-based piezoelectric materials [4][5][6][7][8][9][10]. Some piezoelectric polymers like cellulose and their derivative, polyurethanes (PU), polyimides (PI), polylactic acid (PLA), polyvinylidene fluoride (PVDF) and its copolymers, etc.…”
Section: Introductionmentioning
confidence: 99%
“…13 In addition, reports have shown that porous structures have a strong strain response and regular charge distribution aer poling, facilitating the conversion of force to electricity. [14][15][16][17][18] The methods for preparing porous PVDF generally involve the hard template method, sol-gel method, and solution method. 14,15,19 Seung et al 20 prepared PVDF nano cell arrays through a template-assisted method, which were applied in nanogenerators.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] The methods for preparing porous PVDF generally involve the hard template method, sol-gel method, and solution method. 14,15,19 Seung et al 20 prepared PVDF nano cell arrays through a template-assisted method, which were applied in nanogenerators. The porous PVDF nanogenerator delivered high rectied power density (0.17 MW cm À3 ), and its piezoelectric potential and current increased 5.2 and 6 times, respectively, in comparison to the 2D PVDF lm.…”
Section: Introductionmentioning
confidence: 99%